A paradigm shift? The Sustainable Development Goals in corporate sustainability reporting from an organisational legitimacy perspective: The case of France’s 50 largest companies - Robin, Marc (2017)
The United Nations Sustainable Development Goals (SDGs) were globally adopted in 2015 and define the sustainable development roadmap to 2030. For the goals to be reached, everyone needs to do their part, including the private sector. In that regard, the United Nations has made clear that corporate reporting on the SDGs is key to help achieve this global agenda, hence widely regarded as a major shift for corporate sustainability reporting. However, two years after their advent, and despite the urgency and the scale of this task, no academic research has actually addressed how companies have reported on their voluntary implementation of the SDGs. Thus, this thesis intends to fill this research gap, hopefully encouraging the development of a new research agenda and providing more visibility for policymakers. Focusing on the 50 largest French companies, it explores whether they have reported on the SDGs, how they have done so, and proposes the use of the organisational legitimacy theory to try to understand this phenomenon. To conduct this study, which contributes to the social and environmental accounting literature, the approach adopted was a content analysis of the companies’ most recent public disclosures available on their websites. The findings reveal that more than half of the 50 largest French companies have at least mentioned the SDGs in their disclosures. However, how to report on them and for whom does not seem to be clear for the companies, and the results are quite disparate overall. Also, ambiguities of accountability have been identified and the companies have mainly undertaken a symbolic approach to enhance their legitimacy by reporting on the SDGs.